Analysis of Three Forms of Power by Joseph Nye. (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
The politics of international relations since the end of the Second World War have been preoccupied with the business of mitigating chances of war among nations. The Liberal tradition proposed three solutions to this effect, including democracy, economic interdependence, and international institutions. Neoliberalism, championed by Joseph Nye and Keohane advancing the liberal course, upholds the existence of anarchy within the international system but insists that that does not prevent cooperation. This led them to develop the notion of complex interdependence. It is within the ambience of this principle of complex interdependence that Joseph Nye developed his idea of three types of power. This work therefore is set to examine these three forms of power. According to him, there is hard, soft, and smart power. The data for this research is collected through library research. By analysing Nye’s three forms of power, it was discovered that Nye introduced the third type or concept, smart power, as a means of smuggling hard power through the backdoor to override soft power. Acknowledging the defects of soft power, the paper is of the opinion that there will be greater peace in the international arena if nations can deploy the resources of soft power in their engagements. However, nations with greater military and economic resources are more prone to deploying their military might in settling international disputes than their soft power resources. Whether knowingly or unknowingly, Nye has given those with greater military powers a soft landing to deploy their hard power by the tool of smart power, which he argues can be deployed under contextual intelligence.